Deaths related to post-COVID in Italy: a national study based on death certificates - Grippo, Francesco; Minelli, Giada; Crialesi, Roberta; Marchetti, Stefano; Pricci, Flavia; Onder, Graziano (Frontiers in Medicine, 2024)
Introduc on: SARS-CoV-2 infec on has been associated with the onset or persistence of symptoms in the long-term a er the acute infec on is resolved. This condi on known as Post-COVID, might be par cularly severe and poten ally life-threatening. However, li le is known on the impact of post-COVID condi on on mortality. Aim of the present study is to assess and quan fy Post-COVID deaths in Italy in years 2020 and 2021, based on an analysis of death cer ficates.Methods: Data from the Italian Na onal Cause of Death Register were analyzed. ICD-10 code U09.9, released by the World Health Organiza on in September 2020, was used to iden fy the 'Post-COVID' condi on.Numbers of post-COVID deaths from October 2020 to December 2021 were analysed. Rates of post-COVID deaths were calculated for the year 2021.Results: Between October 2020 and December 2021, 4,752 death cer ficates repor ng post-COVID condi on were iden fied. Of these, 14.9% (n=706) occurred between October and December 2020 and 85.1% (n=4,046) in 2021. In 46.0% of post-COVID-related deaths, the underlying cause of death was COVID-19. Other frequent underlying causes were heart disease (14.3% of cases), neoplasms (9.2%), cerebrovascular diseases (6.3%) and Alzheimer's disease and other demen as (5.5%). The mortality rate related to post-COVID condi ons in year 2021 was 5.1 deaths per 100 thousand inhabitants and it increased with increasing age.Men showed a higher mortality rate than women (4.3 deaths per 100 thousand in women and 6.0 deaths per 100 thousand in men).Discussion: Post-COVID condi ons contributed to a substan al number of deaths in Italy. Strategies to iden fy the popula on at risk of severe long-term consequences of SARS-CoV-2 infec on and interven ons aimed at reducing this risk must be developed.